1999
DOI: 10.1002/(sici)1520-6300(1999)11:4<469::aid-ajhb6>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressures of Sherpa men in modernizing Nepal

Abstract: The relationship among potential risk factors (diet, adiposity, physical activity levels (PALs), and age) for elevated blood pressures (BP) was examined in 253 Sherpa men living in Kathmandu (low altitude sample: LAS) and in the Khumbu (high altitude sample: HAS) regions of Nepal. The study is based on data collected to assess nutritional status. Elevated BPs were highly prevalent among both samples of men (LAS: 21.7% and HAS: 24.8%). The highest percentage of elevated BP was found among the urban HAS (32.4%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 30 publications
(35 reference statements)
4
20
1
Order By: Relevance
“…In a country as poor as Nepal, with a high prevalence of undernutrition (Gautam, 1996), a heavy infectious disease load and very high child mortality rates (United Nations, 1993), it is perhaps surprising to find clear evidence of changes in cardiovascular characteristics normally associated with affluence. However, similar findings have been observed for adults (Smith, 1999). The findings show that lifestyle changes produce potentially deleterious effects on blood pressure from an early age.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In a country as poor as Nepal, with a high prevalence of undernutrition (Gautam, 1996), a heavy infectious disease load and very high child mortality rates (United Nations, 1993), it is perhaps surprising to find clear evidence of changes in cardiovascular characteristics normally associated with affluence. However, similar findings have been observed for adults (Smith, 1999). The findings show that lifestyle changes produce potentially deleterious effects on blood pressure from an early age.…”
Section: Discussionsupporting
confidence: 85%
“…For instance, Pawson et al (1984) noted that tourism has had a huge impact on the economy of the district capital of the Everest region, and contrasted it to the lack of change in nearby villages which were not on the main Everest trail. Working in this area, Smith (1999) compared the blood pressure of Sherpa men living in urban and rural locations and also compared these re-sults with those from Sherpa men living in Kathmandu, the capital. She showed that blood pressure levels were higher than in a survey of 30 years ago, having reached levels similar to those seen in the United States, and found that urban living was associated with higher diastolic blood pressure.…”
mentioning
confidence: 99%
“…Although it was not possible to corroborate self-reported grain consumption, the estimated minimal energy intake of adult male porters from their own provisions, roughly 2,700-2,800 kcal (11.3-11.7 MJ) per day, was consistent with the average daily intake of at least 2,500 kcal/capita from their own rice previously estimated for a larger sample of 453 male and female porters ages 10-65 years (Malville, 1999). These estimates of minimal energy intake from the porters' own supplies equal or exceed the total daily caloric intakes of 2,200 to 2,700 kcal reported for subsistence farmers elsewhere in the hills of Nepal (Brown et al, 1968;Gautam, 1984;Koppert, 1988;Panter-Brick, 1996b;Smith, 1999). The porters obtained additional energy from prepared food purchased at teahouses along the route.…”
Section: Energy Expenditure Of Porters In Nepalsupporting
confidence: 65%
“…The majority (70%) of the hill porters in eastern Nepal are members of Tibeto-Nepali hill tribes such as Tamang, Rai, Sherpa, and Gurung, with lesser participation by Newars and high-and low-caste Hindus of Indo-Nepali origin (Malville, 1999). Sherpa males, who are frequently involved in businesses catering to foreigners, such as adventure tourism and operation of trekkers' lodges (Fü rer-Haimendorf, 1984;Fisher, 1990;Smith, 1999), are more likely to be the hill shopkeepers hiring the porters rather than the bearers of loads.…”
mentioning
confidence: 99%
“…Two major ethnic populations living at HA in Nepal are Tibetans and Khas-Aryas. Particularly those from Tibetan origins (such as Sherpa and Thakali) have culturally derived food practices of consuming large amounts of alcohol, salt, meat products and oil [9]. We hypothesized that physiological responses from chronic exposure to the hypoxic environment of HA may result in adverse effects on lipid profiles and diet and lifestyle factors of HA residents of Nepal may increase average blood glucose levels, despite metabolic adaptation.…”
Section: Introductionmentioning
confidence: 99%